Intersection of performative and choreographic arts of the Eastern Europe early in the 21st century - Shabalina, O. M. (My University, 2017)
The research is related to the search for new means and methods of justifying the aesthetic and ethical-moral norms as the ground for analysis of the principles and devices of performative techniques in contemporary dance art. The crisis of certain development models of contemporary dance art does not always consider the place and the role of an experiment in perceiving the emergence of choreographic lexis and the conflict of social, political and spiritual transformation in the dance art. There is a comparative review of contemporary Polish art performances, which exploit different principles and techniques for interaction with the audience and the space on the base of the individual creative work of Polish choreographers. The research studies the principles and devices of performative techniques as the instrument of emotional and social expression of an individual within the emotionally oriented environment with the help of verbal interaction with the perception object.
Keywords: сучасний танець; хореографічна лексика; перформанс; контемпорарі; contemporary; modern dance; choreographic vocabulary; performance